Prevalence of mecC Gene in MRSA at A Tertiary Hospital in Medan, Indonesia - Fiola Elsabillah Amandani; Sri Amelia; Nurfida Khairina Arrasyid; Fera Wahyuni; Ridwan Balatif (Journal of Pure and Applied Microbiology)
Methicillin-resistant Staphylococcus aureus (MRSA) is resistant to β-lactam antibiotics owing to the presence of mecA and mecC resistance genes. Resistance genes in MRSA are carried by a genetic component named staphylococcal cassette chromosome mec (SCCmec). The mecC gene showed 63% similarity with the mecA gene. This resulted in the mecC gene not being detected by routine PCR examination, which specifically detects mecA. Data regarding the epidemiology of molecular detection of the mecC gene in Indonesia are still very limited, especially in North Sumatra Province. This study aimed to characterize MRSA resistance genes in a tertiary hospital in Medan, North Sumatra. Clinical samples of the infection were collected and identified as MRSA using the VITEK-2 compact device. A total of 80 samples from bacteremia patients in our hospital were used in this research. The detection of resistance genes is performed using conventional Polymerase Chain Reaction (PCR). Visualization of the presence of genes was performed using electrophoresis. The mec gene was detected in 79 MRSA samples (98.75%). A total of 63 samples carried two resistance genes, mecA and mecC (78.75%), 15 samples carried only mecC (18.75%), one sample carried only mecA, and only one sample carried neither mecA nor mecC. The finding of the mecC gene is a cause for concern because it cannot be detected via routine PCR. This study showed that the majority of MRSA bacteria carry a mixture of mecA and mecC genes.